Unblocking Barriers of Access to Hepatitis C Treatment in China: Lessons Learned from Tianjin - Peiwen Zhang (Ubiquity Press, 2020)
Background: The high price is a critical barrier of access to new direct-anting-antiviral (DAA) therapies for hepatitis C for both the patients and the society. Many countries continue to face the challenge of financing such expensive medicines. Such examples include both high-income and middle-income countries. Existing evidence about the efforts of China to address this challenge is limited. To our knowledge, this is the first detailed description of a novel financing model and comprehensive analysis of its impact on patient financial burden of hepatitis C treatment in China. Objective: To examine the evolution of approaches to navigating patients’ barriers of access to DAA-based treatment of hepatitis C in Tianjin City, China. Methods: Review of publicly available literature, including published and grey literature. Conduct on-site data extraction and key informant interview. The patient financial burden of hepatitis C treatment was analyzed. The financial burden of hepatitis C patients with different treatment models and health insurance financing models was measured by calculating the number of annual income to cover patient out-of-pocket (OOP) expenditure for the standard treatment course accordingly. Findings: Tianjin is the first area to pilot a capitated provider payment program for the treatment of hepatitis C. Through which, the retirees and employees spend 0.7 and 1.0 months of their salary, and residents spend 5.6-6.8 months of their salary for the treatment, the financial burden of patients were much relieved. By the end of March 2019, the first-year pilot program had 876 hepatitis C patients registered the new insurance coverage and treated in Tianjin. Conclusions: The study showed that the financial barriers of access to new hepatitis C treatment for patients could be unblocked with government commitment and novel financing models. International experiences demonstrated that centralized bulk procurement is a good leverage for price negotiation, primarily when using innovative payment approaches. To replicate the initial success of Tianjin, continued efforts are needed for stronger strategic price negotiation, preferably at central level. The case of Tianjin brings implications to the other areas of China and even other developing countries that government commitment, novel financing model and pooled procurement are critical elements of stronger purchasing power and a better secure of treatment.